(untitled) (Bangladesh Journal of Agricultural Research, 2009)
Two field experiments were carried out during two consecutive rabi seasons of 2002-03 and 2003-2004 at Farming System Research Site, Chabbish Nagar, Rajshahi (AEZ 11) with a view to assessing the effect of Rhizobium inoculation on four varieties of chickpea viz., BARI Chola-3, BARI Chola-4, BARI Chola-5 and BART Chola-6. Each variety was tested with and without Rhizobium inoculation. Each plot received basal application of 22 kg P/ha as TSP, 42 kg K/ha as MOP, 20 kg S/ha as gypsum and 5 kg Zn/ha as zinc oxide. Peat based rhizohial inoculurn (Rhizohium strain RCa-220) @ 1.5 kg/ha was used for seed inoculation. Inoculated plants gave significantly higher nodule number, nodule weight, stover yield and seed yield compared to uninoculated plants. Among four varieties, BARI Chola-3 produced the highest nodule number, nodule weight and stover yield, while the highest yield was obtained from BARI Chola-4. Key Words: Chickpea, Rhizobium, nodulation, yield. doi: 10.3329/bjar.v33i4.2287 Bangladesh J. Agril. Res. 33(4) : 549-554, December 2008